‘Dalia’, a new variety of bean grain, Flor de Junio type for the central region of Mexico - Acosta-Gallegos, Jorge Alberto; Montero-Tavera, Víctor; Jiménez-Hernández, Yanet; Anaya-López, José Luis; Gonzalez-Chavira, Mario Martín (Revista Mexicana de Ciencias Agrícolas, 2018)
Flor de Junio has grains of cream colored background with pink stripes; it is produced and consumed in the central region of Mexico. We describe the process for its gathering and Dalia ́s features, a new variety of bean grain, Flor de Junio type, Jalisco race, obtained from the cross of Flor de Junio Silvia X Flor de Mayo Anita performed in the Bajío Experimental Field in 2003. The selection process was initially based on health and the cycle of the plant, as well as the commercial properties in grain crops under alternative irrigation and rainfed conditions. In its final phase, we conducted an assisted molecular marker selection (AMS) for selecting the offspring that had simultaneously the markers ROC11 and SW13, linked to genes I and bc3, whose pyramiding confers resistance to all pathotypes of BCMV and BCMNV viruses. Dalia has an indeterminate growth habit type 3, with medium size guides and intermediate growing season with 105 days from sowing for physiological maturity and is resistant to BCMV and BCMNV. In a national assessment of yield and adaptation, Dalia showed similar yielding of Flor de Junio Marcela, the dominant variety within the market, but contrasting with this, a none existent G*E interaction, which indicated a high adaptation and yield stability. Dalia is recommended for irrigated and rainfed production in the regions of El Bajío and highlands of central Mexico.
Keywords: Phaseolus vulgaris L.; adaptation and stability; disease resistance; AMS